ChemInform Abstract: 3‐Oxyanthranilic Acid Derivatives from Actinomadura sp. BCC27169. Issue 36 (9th September 2014) - Intaraudom, Chakapong; Dramae, Aibrohim; Supothina, Sumalee; Komwijit, Somjit; Pittayakhajonwut, Pattama
Abstract Compounds (IIa) and (IVb) exhibit antitubercular activity, (IIa) also shows cytotoxicity against KB cells.